ANALISIS SISTEM DAN PROSEDUR PEMUNGUTAN PAJAK DAERAH DALAM UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH PADA BADAN PELAYANAN PAJAK DAERAH - Amyati, Amyati; Hikmawati, Sri Ratu (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
The implementation of regional autonomy has spurred the Pandeglang district government to be creative in finding sources of regional revenue that can support regional financing. Regional Tax is one source of regional income that can be extracted in the context of increasing Regional Original Income. The purpose of the study was to determine the implementation of local tax collection systems and procedures in an effort to increase PAD, to determine the implementation of the Pandeglang Regency Regional Regulation Policy Number 3 of 2018 concerning Regional Taxes, to determine the increase of Pandeglang Regency's PAD in 2016-2020. The method used is descriptive qualitative method. The type of data used is primary data in the form of interviews and secondary data in the form of targets and realization of regional taxes, targets and realization of PAD in 2016 - 2020. The procedure applied to local tax collection consists of 9 main activities, registration, determination, deposit, application for installments, bookkeeping and reporting, objections and appeals, collection, correction, and collection of overpayments. The implementation of Regional Regulation No. 3 of 2018 concerning Regional Taxes has not fully implemented the Government's Internal Control System. The increase in PAD from year to year has increased fluctuations. Conclusion The system and procedure for collecting local taxes at the Regional Tax Service Agency of Pandeglang Regency are in accordance with existing regulations. BP2D of Pandeglang Regency uses Perda No. 3 of 2018 as one of the guidelines in making decisions and determining policies. Overall in five years the components of local taxes that contributed the most to the increase in PAD were PBB P2 Tax, BPHTB Tax and Street Lighting Tax